2014
DOI: 10.17795/nmsjournal21764
|View full text |Cite
|
Sign up to set email alerts
|

High-Flux and Low-Flux Membranes: Efficacy in Hemodialysis

Abstract: Background: Inadequacy of dialysis is one of the main causes of death in hemodialysis patients. Some studies have suggested that highflux membrane improves the removal of moderate-sized molecules while other studies indicate no significant effect on them. Objectives: This study aimed to investigate the dialysis efficacy of low-flux versus high-flux membranes in hemodialysis patients. Patients and Methods: Forty hemodialysis patients participated in this cross-over clinical trial. Two sessions of low-flux and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
0
29
0
2
Order By: Relevance
“…Further, incorporation of NZ in PT‐NZ HFMs also resulted in increased pore density with size desirable for high water flux . It may be noted that high flux dialyzer membranes not only improve the quality of dialysis but also shorten dialysis time . Thus, PT‐NZ HFMs with high K UF showed remarkably improved uremic toxins removal rate than that of the remaining HFMs, as demonstrated later in the article.…”
Section: Resultsmentioning
confidence: 76%
“…Further, incorporation of NZ in PT‐NZ HFMs also resulted in increased pore density with size desirable for high water flux . It may be noted that high flux dialyzer membranes not only improve the quality of dialysis but also shorten dialysis time . Thus, PT‐NZ HFMs with high K UF showed remarkably improved uremic toxins removal rate than that of the remaining HFMs, as demonstrated later in the article.…”
Section: Resultsmentioning
confidence: 76%
“…7,9) The use of highflux non-cellulose membrane with increased permeability enables the removal of moderately sized molecules (10,000-15,000 Da), including many of the inflammatory proteins, β-2 microglobulin, and lipoproteins, from the body. 10,11) In this case, due to the long-standing HD history, the patient had been on traditional HD until the full-blown destructive DRA developed. Several reports have noted that DRA is related to the duration of HD and can be cured by kidney transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Thereby, dialysis adequacy has significantly increased in highflux dialysis compared to routine dialysis. Several studies reported an effective improvement in dialysis adequacy using high-flux filter (25,26). Werner et al also reported more suitable clinical outcomes using high-flux filters than routine dialysis (27).…”
Section: Discussionmentioning
confidence: 99%